Development and quality evaluation of functional shrikhand - K. Reshma Ramakrishnan; K. Radha; S.N. Rajakumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Functional shrikhand varieties such as low calorie and low fat shrikhand were developed by incorporation of stevia as low calorie sweetener and when protein concentrate as a fat replacer respectively. Low calorie shrikhand was prepared by incorporating stevia at different levels [0.025% (T1), 0.05% (T2) and 0.1% (T3)]. Shrikhand samples were evaluated based on physicochemical, microbiological and sensory qualities. There was no significant difference in titratable acidity and ash content but the total solids and protein content were significantly lower in low calorie shrikhand. The yeast and mould count increased and coliform count decreased during storage. The sensory quality of low calorie shrikhand was comparable to control. Low fat shrikhand samples were prepared by using WPC at three different levels [1(T1), 1.5(T2) and 2(T3) per cent]. Control shrikhand was prepared from skim milk without the addition of WPC. There was no significant difference in ash content. But there was a significant difference in acidity, total solids, protein and fat content between control and treatment samples. The yeast and mould count increased during storage but coliform count decreased during storage. The sensory quality of low fat shrikhand was similar to that of control.